The Influence of Service Quality And Price on Customer Loyalty With Customer Satisfaction as A Moderator Variable on Maxim online Transportation Users - Augustine, Nuraini Maya; Putra, Andala Rama (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The presence of online transportation providers has increased rivalry in Indonesia's transportation sector. However, many students remain dissatisfied with the services of the online transportation industry, particularly Maxim. This research seeks to explore the connection between service quality, pricing strategies, and customer loyalty, with customer satisfaction acting as an intermediary variable. The proposed framework was tested among Bandar Lampung University students who use the Maxim application. An online survey was conducted with 280 students aged 19 to 25 years from Bandar Lampung University as participants. The data were analyzed using SmartPLS 3.0, applying structural equation modeling to test the model and evaluate the hypotheses. The first and second hypotheses were validated, showing that service quality and pricing positively influence customer loyalty. Similarly, the third and fourth hypotheses were supported, revealing that service quality and pricing significantly enhance customer satisfaction. The fifth hypothesis was corroborated, demonstrating that customer satisfaction strengthens customer loyalty. Furthermore, the sixth and seventh hypotheses were confirmed, demonstrating that customer satisfaction serves as a mediator in the relationship between service quality, pricing strategies, and customer loyalty. This study revealed that service quality and pricing play a vital role in shaping Maxim's customer loyalty, particularly among students at Bandar Lampung University. Customer satisfaction acts as a moderating factor that reinforces the relationship between service quality, pricing, and customer loyalty. The findings highlight that customer satisfaction significantly impacts the intention to reuse the service, underscoring the critical role of trust and positive user experiences in fostering customer loyalty. This study investigates the influence of service quality and pricing on customer loyalty among Maxim online transportation users, with customer satisfaction serving as a mediating variable. Additionally, it explores how satisfaction enhances the connection between service quality, pricing, and customer loyalty.